Pengaruh Upah Minimum Provinsi, Inflasi dan Jumlah Penduduk Terhadap Produk Domestik Regional Bruto di Provinsi Sumatera Utara - Yustia Saputri; Umaruddin Usman (Jurnal Ekonomi Regional Unimal, 2020)
This study aims to determine and analyze the influence of Provincial Minimum Wage, Inflation, and Total Population in North Sumatra Province. The data used in this study are secondary data for 19 years (2000-2018). The method of data analysis used is multiple linear regression with the help of Eviews 10. The results partially show that provincial minimum wage has a positive and significant effect on gross regional domestic products in North Sumatra province, inflation has a negative and insignificant effect on gross regional domestic products, and total population has a positive and insignificant effect on gross regional domestic products. Simultaneously, the provincial minimum wage, inflation, and total population have a positive and significant effect on gross regional domestic products.Keywords: Gross Regional Domestic Products, Provincial Minimum Wage, Inflation, and Total Population.